SOC Estimation Using Deep Bidirectional Gated Recurrent Units with Tree Parzen Estimator Hyperparameter Optimization - How D.N.T.; Hannan M.A.; Lipu M.S.H.; Ker P.J.; Mansor M.; Sahari K.S.M.; Muttaqi K.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Battery management systems; Charging (batteries); Computer architecture; Digital storage; Heuristic methods; Lithium-ion batteries; Long short-term memory; Temperature measurement; Trees (mathematics); Bidirectional gated recurrent unit; Computational modelling; Deep learning; GRU; Hyper-parameter; Learning models; Optimisations; Parzen estimators; State-of-charge estimation; States of charges; Optimization